Investigation of Natural Convection in a Vertical Cavity Filled with a Anisotropic Porous Media - Sayed Mojtaba Muasavi; Mohammad Reza Shahnazari (Iranian Journal of Chemistry & Chemical Engineering, 2008)
In present paper, a numerical analysis for a rectangular cavity filled with a anisotropic porous media has been studied. It is assumed that the horizontal walls are adiabatic and impermeable, while the side walls of the cavity are maintained at constant temperatures and concentrations. The buoyancy force that induced the fluid motion are assumed to be cooperative. In the two extreme cases of heat-driven (N  1) and solute-driven (N  1) natural convection, scale analysis is applied to predict the order of magnitudes involved in the boundary layer regime. Especially, the effects of anisotropic properties on heat and mass transfer have been considered. The variation of Nusselt and Sherwood numbers for values of permeability ratio for a wide range of thermal Rayleigh number, buoyancy ratio, and Lewis number are presented. It is demonstrated that the anisotropic properties of the porous medium considerably modify the heat and mass transfer rates from that expected under isotropic conditions.